2015
DOI: 10.1016/j.procs.2015.08.599
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Business Intelligence on the Quality of Decision Making – A Mediation Model

Abstract: Business Intelligence (BI) systems have been a top priority of CIOs for a decade, but little is known about how to successfully manage those systems beyond the implementation phase. This paper investigates the direct and indirect effects of BI management quality on the quality of managerial decision making using PLS analysis of survey responses of senior IT managers in Australia. The results confirm this overall relationship (total effect), but also reveal mediating effects of data/information quality and BI s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 36 publications
3
54
0
1
Order By: Relevance
“…Information assists in decision-making by reducing uncertainties and removing assumptions. It can be used to predict consequences of a choice or action through a technique called 'simulation' (Wieder & Ossimitz 2015). A study on six large organisations showed that the master data was a strategic asset which added to the competitive capability of the firm with regard to the resource based view (Otto 2015).…”
Section: Information Qualitymentioning
confidence: 99%
See 3 more Smart Citations
“…Information assists in decision-making by reducing uncertainties and removing assumptions. It can be used to predict consequences of a choice or action through a technique called 'simulation' (Wieder & Ossimitz 2015). A study on six large organisations showed that the master data was a strategic asset which added to the competitive capability of the firm with regard to the resource based view (Otto 2015).…”
Section: Information Qualitymentioning
confidence: 99%
“…However, high information quality requires a high level of data quality. Thus, managing data is paramount to ensure trust in the BI system as a whole (Wieder & Ossimitz 2015;Wixom & Watson 2001).…”
Section: Information Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…In [24] the authors emphasize the influence of the quality of data management in business intelligence (BI) systems throughout the whole process form the sources to the decision making stage. In [25] the impact that DQ has on decision making, organizations believability and customer satisfaction is remarked.…”
Section: How Dq Is Managed In Dws?mentioning
confidence: 99%